IDENTIFIKASI KARAKTERISTIK POTENSI PENGEMBANGAN PARIWISATA CURUG GONDORIYO, KECAMATAN NGALIYAN, KOTA SEMARANG - Sudrajat, Agus Sarwo Edy (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2024)
Tourism is starting to be glimpsed by the community as one of the sectors that promises to be on a global scale from the development of tourism. With various kinds of tourism, community-based tourism emerges by utilizing natural resources in the surrounding environment. In addition, in the development of tourism which contributes to increasing tourist visits to an area, it also has an impact on the socio-economics of the surrounding community. One of the tourism development potentials managed by the Gondoriyo Waterfall is located in Karang Joho Hamlet, Gondoriyo Village, Ngaliyan District, Semarang City. The purpose of this research is to identify the characteristics of the tourism development potential of Curug Gondoriyo, Ngaliyan District, Semarang City. The method used in this research is descriptive qualitative based on the results of field orientation (primary) and interviews (secondary). Based on the research conducted, it can be seen the number and condition of the availability of 5 tourism infrastructures consisting of roads, clean water, solid waste, energy, and telecommunications based on SNI tourism standards. In addition, it is known the main tasks and institutional functions of POKDARWIS in the development of Curug Gondoriyo tourism as well as the role of the government in participating in the management and development of tourism. And analyze based on tourism components, namely attractions, accessibility, facilities and supporting Services.